Teori Hukum Tentang Kerugian Negara yang Nyata dan Pasti - Ahmadie Azra Isnain (LPPM Universitas Ekasakti Padang, 2023)
The uncertainty of the interpretation of state losses has created debate between law enforcement officials and legal experts. The lack of a theoretical basis means that the interpretation of state losses can be influenced by legislation made by the authorities. In state losses, it must be carefully emphasized that there is a real and certain state loss, not just an assumption, indication or potential. State finances that are used for the public interest make the flow of money must be supervised by an independent institution so that the Financial Supervisory Agency (BPK) is formed, the audit report on the financial statements of the government or institution will be reported to the House of Representatives as transparency in the audit. BPK as a government agency assigned to assess and calculate state losses, aims to detect deviations from the provisions of laws and regulations, fraud and non-compliance (abuse). BPK's conclusion on state losses can be in the form of mal-administration and unlawful acts. State losses in the exercise of authority, terms and procedures are the substance of administrative actions, while the existence of bribery, coercion, and deception in the presence of unauthorized and unlawful receipts is the substance of criminal acts.